Adoption of Green HRM Practices by Industrial Sectors in Kathmandu Valley (Quest Journal of Management and Social Sciences, 2026)
Background: Green HRM is an emerging concept, but limited research has explored the relationship between Green Human Resource Management (HRM) practices and organizational commitment. Existing literature shows a gap in understanding how Green HRM is implemented in industrial sectors and its impact on employee abilities, creativity, and commitment.Purpose: The study aims to examine the level of implementation of Green HRM practices in industrial sectors of Kathmandu Valley and analyze their relationship with organizational commitment, extending the Ability–Motivation–Opportunity (AMO) framework.Design/Methodology/Approach: An explanatory research design was adopted, and data was collected using a structured questionnaire. A total of 144 responses were analyzed quantitatively using descriptive and inferential statistics. Smart-PLS 4.0 was applied to assess relationships between Green HRM practices, green human capital, and organizational commitment.Findings: The study reveals that Green HRM practices are rarely implemented in industrial sectors of Kathmandu Valley, with medium-scale industries adopting them more than small-scale industries. Green human capital has a significant positive relationship with organizational commitment, while Green HRM practices enhance employee abilities and green creativity but shows an insignificant relationship with organizational commitment.Conclusion: The findings highlight the importance of Green HRM practices in enhancing employee capabilities and fostering creativity. The study provides practical insights for manufacturing industries, HR managers, policymakers, researchers, and students seeking to promote sustainable HR practices in the industrial sector.Key words: GHRM, Organizational Commitment, Green Human Capital, Mangers/ Owners, Kathmandu Valley Industrial Estate, AMO Theory